Cartridges and firearm identification - Walker, Robert E. (Boca Raton, Florida : CRC Press, 2013)
'This book provides essential practical information about firearms and ammunition in a clear, easy-to-follow format. Presenting general rules and practices, the text provides a methodology for identification of unknown firearms and ammunition of questioned identity. The author explains the terminology and describes each group of firearms and the aspects that identify the weaponry, such as property marks, proof marks, and patent dates. This comprehensive reference includes case studies, color and black-and-white photographs, and illustrations to illuminate and support the text'--
Includes bibliographical references (pages 337-342) and index.
Includes bibliographical references and index.
Keywords: Cartridges -- Identification; Evidence, Expert; Firearms -- Identification